Mining Indole Alkaloid Synthesis Gene Clusters from Genomes of 53 Claviceps Strains Revealed Redundant Gene Copies and an Approximate Evolutionary Hourglass Model - Liu, Miao; Findlay, Wendy; Dettman, Jeremy; Wyka, Stephen A; Broders, Kirk; Shoukouhi, Parivash; Dadej, Kasia; Kolařík, Miroslav; Basnyat, Arpeace; Menzies, Jim G (Toxins, 2021)
Ergot fungi (Claviceps spp.) are infamous for producing sclerotia containing a wide spectrum of ergot alkaloids (EA) toxic to humans and animals, making them nefarious villains in the agricultural and food industries, but also treasures for pharmaceuticals. In addition to three classes of EAs, several species also produce paspaline-derived indole diterpenes (IDT) that cause ataxia and staggers in livestock. Furthermore, two other types of alkaloids, i.e., loline (LOL) and peramine (PER), found in Epichloë spp., close relatives of Claviceps, have shown beneficial effects on host plants without evidence of toxicity to mammals. The gene clusters associated with the production of these alkaloids are known. We examined genomes of 53 strains of 19 Claviceps spp. to screen for these genes, aiming to understand the evolutionary patterns of these genes across the genus through phylogenetic and DNA polymorphism analyses. Our results showed (1) varied numbers of eas genes in C. sect. Claviceps and sect. Pusillae, none in sect. Citrinae, six idt/ltm genes in sect. Claviceps (except four in C. cyperi), zero to one partial (idtG) in sect. Pusillae, and four in sect. Citrinae, (2) two to three copies of dmaW, easE, easF, idt/ltmB, itd/ltmQ in sect. Claviceps, (3) frequent gene gains and losses, and (4) an evolutionary hourglass pattern in the intra-specific eas gene diversity and divergence in C. purpurea.
Keywords: Indole Alkaloids; molekulární evoluce; ergot fungi; gene diversity; ergot alkaloids; Ergot Alkaloids; Phylogeny; Evolution, Molecular; secondary metabolites; indole diterpenes; indolové alkaloidy; námelové alkaloidy; fylogeneze; geny hub; Claviceps; phylogeny; gene divergence; Genes, Fungal; multigenová rodina; Multigene Family